Lighting design affects the uniformity and growth of plants in a vertical farming system - Jang, Seong-Nam; Son, Ki-Ho; Kim, Elio Jin-Ha; Lee, Hee Yul; Cho, Kye Man; Kim, Sorae; Park, Youngsam; Jeong, Jong Bin; Kim, Min Ju; Jung, Jea Gack; et al. (Plant Science Today, 2025)
Light is essential for plant production and has various effects on plant quality. Vertical farms typically use light-emitting diodes (LEDs) as light sources. However, the cost of LEDs varies with wattage and the initial installation costs are generally high. Therefore, to explore more cost-effective LED designs, we aimed to investigate the impact of red LED chips density on light distribution and plant growth under the same total electricity consumption. To this end, we exposed baby leaf soybean (Glycine max (L.) Merr.; 5 days) and kale (Brassica oleracea var. acephala; 18 days) to LEDs light with different arrangements of red and white chips. Plants were exposed to either 2 W chips with a red: white ratio of 4: 64 (2W4R treatment) or 1 W chips with a red: white ratio of 8: 64 (1W8R treatment) across the entire LED bar. We observed that the distribution of red light in the cultivation room differed depending on the density of the red LED chips. We found that arranging low-power red LED chips at narrow intervals resulted in uniform light distribution across the entire cultivation bed, positively affecting crop growth. Baby leaf soybean and kale exhibited uniform growth under 1W8R and growth was particularly enhanced in kale. This may be because of the dense leaf structure of kale, which promotes photosynthesis under a uniform light environment. The results of this study demonstrate that a favorable light environment can be created by altering the position and distribution of red LED chips, thereby inducing uniform growth in plants.